PLURALISME HUKUM DAN URGENSI KAJIAN SOCIO-LEGAL MENUJU STUDI DAN PENGEMBANGAN HUKUM YANG BERKEADILAN SOSIAL - E. Joeni Arianto Kurniawan (Universitas Airlangga, 2012)
‘Justice’, philosophically, is classified into two; legal justice and social justice. Legal justice refers to justice based on the parameters of the rules while social justice may be defined as equality arises from human relation in the existing social structure. Referring to the implementation of the law nowadays, it is likely that justice cannot be achieved by looking only at the legal justice. Providing justice should also count on the aspect of social justice. Most of the time, the problem of social justice is related to the access to justice. It is so because the existing law is unable to serve legal justice via its rules only. In other words, it is undoubtful that the justice is not merely legal problem but also a social problem. Therefore, jurisprudence should expand its doctrinal and normative approach to socio-legal approach. This article analyse the urge and the contribution of social-legal approach as interdisciplinary study which connect normatf aspect of jurisprudence with social study. Aiming to create a study which is able to provide equality access and justice for all, this article takes legal pluralism concept as the entry point.Keywords; Legal-pluralism, legal-study, social justice